Significance of histopathological features in the diagnosis of Budd–Chiari syndrome on liver biopsies - Pallavi Prasad; Anurag Singh; Alka Singh; Prabhaker Mishra; Narendra Krishnani (Indian Journal of Pathology and Microbiology)
Background: Budd–Chiari syndrome (BCS) requires a constellation of clinical, imaging, and histological findings for diagnosis. Liver biopsy serves as a tool for confirming the diagnosis, even though the histological characteristics are not pathognomonic. Aims: To determine which constellation of morphologic findings could aid in establishing a diagnosis of BCS in clinically suspected cases. Materials and Methods: A 5-year retrospective observational study was conducted. The clinical, laboratory, and histological findings of liver biopsies in patients with a clinical diagnosis of BCS were studied. Cases were segregated into two groups on the basis of the number of histological features present. A scoring system was then devised to assess the efficacy of the histological findings in diagnosing BCS. Statistical Analysis Used: The continuous variables were compared using the Mann–Whitney U-test, and categorical variables were compared using the Fisher-exact test. Results: The common histopathological findings were the presence of red blood cells in the space of disse (100%), peri-portal fibrosis (97.1%), sinusoidal dilation (97.1%), portal inflammation (67.6%), centrilobular necrosis (61.8%) and pericellular/sinusoidal fibrosis (61.8%). Comparison between the two groups showed that centrilobular necrosis, lobular inflammation, portal inflammation, central vein fibrosis, and pericellular/sinusoidal fibrosis were significant parameters. No correlation was found between the clinical and laboratory parameters and the two groups. Conclusions: The liver biopsy features in BCS are often nonspecific, and no single feature in isolation is characteristic. A constellation of features (centrilobular necrosis, lobular inflammation, portal inflammation, central vein fibrosis, and pericellular/sinusoidal fibrosis), when present together, indicate the possibility of BCS.